Pemberdayaan dan Sosialisasi Kader Pendampingan Keluarga Untuk Mencegah Stunting pada Anak-anak di Desa Mekarsari Bogor - Rilla Sovitriana; Rimi Gusliana Mais; Sri Sintawati (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2023)
The prevalence in Bogor Regency of stunting cases will decrease in 2021 to 9.89% with the target of 2023 being Stunting Free Bogor Regency. However, in Mekarsari Village there were still 27 stunted children found. Mekarsari Village has a population of 6,392 people with a maximum education level of high school. In 2021, there will be 1,713 people who have not found work, causing low awareness of health and the family economy. This results in inadequate family nutrition and stunting in children. The aim of Community Service by Empowering and Socializing Family Assistance Cadres to Prevent Stunting in Children in Mekarsari Village, Bogor is one of them. Increasing community knowledge, especially parents and families, about the importance of balanced nutrition and good nutritional practices for optimal growth of children.